(untitled) - Odum, Howard T. (New York, 1996)
This book, introduces the concept of emergy as a way of placing the value of commodities, services, and environmental goods of various kinds on a common basis. The conflicts between economic development and protection of the environment are important political and public policy issues. The aim of this book is to place environmental decision making on a more rational and less emotional basis by finding a common measure of the value of environmental and other kinds of assets.
Keywords: Natural resources,Environmental auditing; Accounting